Modeling PrPSc Generation Through Deformed Templating - Spagnolli, Giovanni; Rigoli, Marta; Novi Inverardi, Giovanni; Codeseira, Yaiza B.; Biasini, Emiliano; Requena, Jesús R. (Frontiers in Bioengineering and Biotechnology, 2020)
Deformed templating is the process by which self-replicating protein conformations with a given cross-β folding pattern can seed formation of an alternative self-replicating state with different cross-β folding pattern. In particular, uninfectious but propagative PrP amyloid transforms into a bona fide infectious conformer, PrPSc, through deformed templating. The process can take many rounds of replication (if taking place in vitro) or even several passages of the evolving PrP conformers through successive brains if in vivo, through experimental transmission. In all cases, deformed templating involves a forced conversion in which there is a mismatch between the template and the substrate and/or the templating environment. Typically, a recombinant PrP amyloid, adept at converting recombinant PrP under denaturing conditions (v.g., presence of chaotropic agents), encountering a glycosylated, GPI-anchored PrPC substrate under physiological conversion conditions. Deformed templating is characterized by emergence of intermediate conformers that exhibit biochemical characteristics that are intermediate between those of the initial PrP amyloid and the final PrPSc conformers. Here, we took advantage of the recent elucidation of the structure of a PrP amyloid by cryo-EM and the availability of a physically plausible atomistic model of PrPSc that we have recently proposed. Using modelling and Molecular Dynamics approaches, we built a complete molecular modelization of deformed templating, including an atomistic model of a glycosylated intermediate conformer and a modified model of PrPSc. Among other unanticipated outcomes, our results show that fully glycosylated PrP can be stacked in-register, and how 4-rung β-solenoid (4RβS) PrP architectures can share key structural motifs with parallel-in register intermolecular sheet (PIRIBS) PrP amyloids. Our results shed light on the mechanisms of prion replication.